Environmental Adult Education and Environmental Stewardship in Nigeria (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper seeks to expose the adult population to the concept of stewardship which utilise diverse actions as creating protected areas, replanting trees, limiting harvests, reducing harmful activities or pollution, creating community gardens, restoring degraded areas or purchasing more sustainable products through the environmental adult education to ensure a proper and effective handling of the environment bearing in mind the essence of God’s provision of the natural resources. The paper examines the part EAE has to play to bring about environmental stewardship in Nigeria such as educating the adult population to be mindful of their dealing with the environment such as sustaining clean and healthy air, protecting and restoring the ecosystems functions, goods and services, generating clean energy and using it effectively, supporting ecological sensitive land management and development among others. It also proffers suggestions that could help us carryout steward behaviour in the society by limiting the way we dispose water bottle after drinking water from the bottle; using a particular item over and over again until it actually becomes a waste; buy or grow our own local food on healthy soil; produce less waste, reduce emitting greenhouse gas to avoid climate change by walking briskly to a short distance among others.